2010
DOI: 10.3109/07420528.2010.489400
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Patterns of Activity of the Orienting and Executive Attention Neuronal Networks in Subjects Performing a Stroop-Like Task: A Functional Magnetic Resonance Imaging Study

Abstract: Attentional processes are fundamental to good cognitive functioning of human operators. The purpose of this study was to analyze the activity of neuronal networks involved in the orienting attention and executive control processes from the perspective of diurnal variability. Twenty-three healthy male volunteers meeting magnetic resonance (MR) inclusion criteria performed the Stroop Color-Word task (block design) in the MR scanner five times/day (06:00, 10:00, 14:00, 18:00, 22:00 h). The first scanning session … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 36 publications
5
40
0
2
Order By: Relevance
“…biasing, the saccade circuitry before the anti-saccade occurrence. The anterior insula has been shown to be a part of the executive system (Klein et al, 2007;Marek et al, 2010) and was found to play a role in response inhibition as well (Brass and Haggard, 2007;Swick et al, 2011). Finally, the thalamus has been associated with the definite inhibition of the prepared action and, consequently, involved in executive operations (Marzinzik and Wahl, 2008).…”
Section: Executive Control Networkmentioning
confidence: 97%
“…biasing, the saccade circuitry before the anti-saccade occurrence. The anterior insula has been shown to be a part of the executive system (Klein et al, 2007;Marek et al, 2010) and was found to play a role in response inhibition as well (Brass and Haggard, 2007;Swick et al, 2011). Finally, the thalamus has been associated with the definite inhibition of the prepared action and, consequently, involved in executive operations (Marzinzik and Wahl, 2008).…”
Section: Executive Control Networkmentioning
confidence: 97%
“…The ROI approach served as a secondary exploration for our primary voxelwise PPI analysis above. In addition to the seed regions within the right DLPFC or PMd used in the primary PPI analyses, we also included regions known to be critical to the functional networks with respect to the DLPFC or the PMd, including inferior parietal cortex for the PMd-seeded networks (Keisker et al, 2009), and supplementary motor area (SMA), inferior frontal gyrus, rostral frontal area, and the contralateral (left) DLPFC for the DLPFC-seeded networks (Marek et al, 2010). Correlations between the IÀR contrast in functional connectivity and the RÀI difference in the mean RT were then tested using the Pearson's correlation method.…”
Section: Lin Et Almentioning
confidence: 99%
“…Marek et al, 2010) showing time of day differences in the ability to regulate strong but incorrect responses in the orienting attentional network -a division of the task-positive network that regulates where and when attention is directed in response to external cues (Schmidt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%